Word Class Errors in English Acquisition Among Chinese EFL Learners: A Conceptual Transfer Perspective - Geng, Wenxin (Ilmu Inovasi Nusantara, 2025)
Word class errors constitute significant speech errors in second language (L2) acquisition, yet researchers often overlook them. Previous studies have only briefly addressed this phenomenon, lacking a deeper exploration of the underlying cognitive aspects. Therefore, this study aims to analyze the acquisition of word classes, specifically nouns, by Chinese learners of English as a Foreign Language (EFL), using data from the TECCL corpus focusing on conceptual transfer. The research method involves corpus data analysis, focusing on word class errors made by learners. This study identifies systematic and regular patterns in these errors through a conceptual transfer approach, indicating the negative influence of conceptual transfer from Chinese grammatical categorization and conceptual attributes on English word class acquisition. These findings offer new insights into conceptual transfer in language acquisition, highlighting the importance of cross-linguistic conceptual influence in teaching English to Chinese speakers. Recommendations include adjusting English language curricula to account for conceptual transfer aspects and implementing teaching strategies that help reduce errors stemming from cross-linguistic conceptual categorization differences. This study is relevant for research on conceptual transfer and holds practical implications for enhancing English language instruction effectiveness among Chinese speakers.